Clinical Insights into Brucella Peritonitis: A Comprehensive Analysis of Four Cases - Shufang Pan; Zulipiya Moming; Abuduweili Awuti; Kaixiang Zhou; Maimaitiaili Tuerxun; Yutian Chong; Jianyun Zhu (Springer, 2024)
Abstract Introduction Brucellosis, a globally distributed zoonotic disease, exhibits diverse clinical manifestations, with Brucella peritonitis being a rare but consequential complication. Methods Analyzing the medical records of four patients with Brucella peritonitis admitted to the First People's Hospital of Kashi Region from January 2022 to November 2023. A retrospective approach was used to analyze the general data, epidemiological history, clinical features, laboratory tests, and efficacy. All four patients with Brucella peritonitis were farmers. Results All of them were combined with decompensated stage of liver cirrhosis. The main manifestations were poor appetite, fatigue, bloating. Two patients were accompanied by moderate-high fever. All patients presented with mildly elevated C-reactive protein and procalcitonin < 0.25ng/ml. Brucella was cultured from blood in 2 cases, from pleural fluid in 1 case, and from ascitic fluid in another case. All patients had moderate-to-large amounts of ascites with elevated leukocytes in the ascites, predominantly mononuclear cells. Symptoms of the above patients were reduced or disappeared after effective anti-infection. Conclusion When patients with decompensated cirrhosis present with exudative ascites dominated by elevated mononuclear cells, the possibility of Brucella peritonitis should also be considered in areas where brucellosis is endemic.